ASPEK-ASPEK YURIDIS DALAM SALVAGE (PENYELAMATAN KECELAKAAN KAPAL) (Faculty of Law, University of Dr. Soetomo, 2018)
Any kind of fortuitiuos events on the sea, such as a distressed vessel could cause financial loss to the master and also damage of the environment. It needs some effort that could be done for minimizing and prevent the impacts of perils of the sea. A principle in salvage called no cure no pay principle, no award for any unsuccessful salvage. That principle, arise a terminology called salvage award. It’s kind of giving reward to those who save the vessel successfully. Indonesia’s marine insurance, is rareto put a salvage as its clause. Practically, salvage is needed. Notwithstanding Indonesia not ratify The Salvage Convention 1989 yet. The attempt to apply its provisions is put the salvage clause in Indonesia’s marine insurance. It’s better if Indonesia ratify that Convention. By put intoit, will anticipate the insurer from the unpredictable loss that may occur.Keywords: Salvage, award, marine insurance.